Type III Interferons: Emerging Roles in Autoimmunity - Manivasagam, Sindhu; Klein, Robyn S. (Frontiers in Immunology, 2021)
Type III interferons (IFNs) or the lambda IFNs (IFNLs or IFN-λs) are antimicrobial cytokines that play key roles in immune host defense at endothelial and epithelial barriers. IFNLs signal via their heterodimeric receptor, comprised of two subunits, IFNLR1 and interleukin (IL)10Rβ, which defines the cellular specificity of the responses to the cytokines. Recent studies show that IFNL signaling regulates CD4+ T cell differentiation, favoring Th1 cells, which has led to the identification of IFNL as a putative therapeutic target for autoimmune diseases. Here, we summarize the IFNL signaling pathways during antimicrobial immunity, IFNL-mediated immunomodulation of both innate and adaptive immune cells, and induction of autoimmunity.